Spatial partitioning of the football pitch based on successful passing paths - Cao, S. (International Journal of Sports Science & Coaching, 2024)
While it is evident that disparities exist across various areas on a football pitch, and numerous studies have investigated spatio-temporal datasets in football for various analyses, there remains a lack of an effective method for quantitatively partitioning the pitch into specific areas with different properties. To address this gap, this article presents a novel approach to partitioning a football pitch into distinct areas based on successful passing paths that lead to goals. Utilizing hierarchical clustering and spatial/temporal features derived from successful passing paths, the study provides multi-level partitions of the football pitch, revealing detailed insights into the relationships between specific areas and scored shots in football games. Empirical analysis of over 4000 successful passing paths from various football leagues and international football events demonstrates the effectiveness of the proposed methodology in identifying and understanding the diverse areas of football pitches. The findings suggest practical applications in football analysis, aiding coaches and specialists in tactics development and informing player positioning and movement strategies.